PENGARUH RESISTANCE EXERCISE DALAM MENURUNKAN KADAR GULA DARAH PASIEN DIABETES : SYSTEMATIC LITERATURE REVIEW - Wahdini, Ridha; Muttaqin, Hanan Siti Maulidah Nurul; Fadilla, Hasna; Abidin, Muhamad Ibni Zaki; Sulastri , Afianti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: Diabetes mellitus is an increasing global health problem, with serious complications that can occur if not properly managed. One widely researched approach is the use of resistance training as a method to control blood sugar levels. Many studies have shown the potential benefits of resistance training, but there are variations in the duration and frequency used. Therefore, this study aims to identify the most effective duration and frequency in such exercise programs Methods: This study used a Systematic Literature Review approach by collecting and analyzing scientific articles from the Elsevier database, Google Scholar, and PubMed using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analysis) method which has gone through four stages, namely identification, screening, eligibility and accepted results. The search resulted in 10 articles that met the inclusion criteria and will be further analyzed for the effectiveness of resistance training in healing diabetes mellitus Results: The results of this review show that resistance training has a significant positive effect in lowering blood sugar levels. Several studies showed a decrease in fasting blood sugar and HbA1c levels after a structured resistance exercise program. Conclusion: These findings support the integration of resistance training programs in diabetes management and make an important contribution to the development of future clinical guidelines.